Caracterização térmica de rochas para utilização em armazenamento de energia térmica - Silva, Walber Morais da (2020)
The present work deals with the thermal characterization a gravel sample, collected in the Brazilian Semiarid, in order to be used in thermal sensitive heat storage systems, offering an alternative material with low cost and high availability. The theoretical and experimental study allows investigating the thermal potential Semiarid stones in northeastern Brazil that can be used as filling materials in the thermal energy storage system at temperatures lower or greater than 100 °C. The experimental apparatus consists of a bench composed of a fixed cylindrical bed, where the thermal conductivity was evaluated by the stationary method and the thermal diffusivity by the transient method. The Bauer and Schlünder models were used to determine the variable identification technique and the conductivity of solid particles. The effect variation in porosity close to the bed wall was considered, as well as the study of the variation particle shapes in the result the thermal conductivity crushed stone. The thermal diffusivity was determined by the experimental method conducting heat in a transient regime, using finite difference method explicit in solution, presented in the unidirectional heat transfer equation in cylindrical coordinates, and the implementation an algorithm in the computer program MATLAB R2016a®. The DSC thermoanalytical technique was used to determine the specific heat crushed stone. Results of conductivity, thermal diffusivity and specific heat in samples crushed stones showed efficiency in the thermal properties, with this, it showed viability in the use thermal sensitive heat storage systems.